EMERGING FACTORS OF ALCOHOL AND SUBSTANCE ABUSE: IMPLICATIONS FOR COUNSELLING - Tambawal, Malami Umar; Tsagem, S. Y. (Sokoto Educational Review, 2020)
This paper discussed the emerging factors of alcohol and substance abuse and how theorists have tried to account for why people use alcohol and other drugs, and especially why they continue or relapse despite negative consequences. Some theories suggest genetic and other biological factors, while others emphasize personality factors or social-environmental factors. While these factors have all been shown to contribute to persistent substance use and to relapse following periods of abstinence, no one set of factors can account for all types of substance use. Rather, substance use appears to result from complex interactions of biological, psychological and social-environmental structures and processes. Some counselling implications suggested were that drug taking could be reduced through a variety of avenues and also by experimenting with biological, psychological and environmental interventions.